Identification of Atypical El TorV. cholerae O1 Ogawa Hosting SXT Element in Senegal, Africa - Sambe-Ba, Bissoume; Diallo, Mamadou H.; Seck, Abdoulaye; Wane, Abdoul A.; Constantin de Magny, Guillaume; Boye, Cheikh S.-B.; Sow, Ahmad I.; Gassama-Sow, Amy (Frontiers in Microbiology, 2017)
Vibrio cholerae O1 is the causative agent of cholera with classical and El Tor, two well-established biotypes. In last 20 years, hybrid strains of classical and El Tor and variant El Tor which carry classical ctxB have emerged worldwide. In 2004-2005, Senegal experienced major cholera epidemic with a number of cases totalling more than 31719 with approximately 458 fatal outcomes (CFR, 1.44%). In this retrospective study, fifty isolates out of a total of 403 Vibrio cholerae biotype El Tor serovar Ogawa isolates from all areas in Senegal during the 2004-2005 cholera outbreak were randomly selected. Isolates were characterized using phenotypic and genotypic methods. The analysis of antibiotic resistance patterns revealed the predominance of the S-Su-TCY-Tsu phenotype (90% of isolates). The molecular characterization of antibiotic resistance revealed the presence of the SXT element, a self-transmissible chromosomally integrating element in all isolates. Most of V. cholerae isolates had an intact virulence cassette (86%) (ctx, zot, ace genes). All isolates tested gave amplification with primers for classical CT, and 10/50 (20%) of isolates carried classical and El Tor ctxB. The study reveals the presence of atypical V. cholerae O1 El Tor during cholera outbreak in Senegal in 2004-2005.